Tinnitus after Simultaneous and Sequential Bilateral Cochlear Implantation - Ramakers, Geerte G. J.; Kraaijenga, Véronique J. C.; Smulders, Yvette E.; van Zon, Alice; Stegeman, Inge; Stokroos, Robert J.; Free, Rolien H.; Frijns, Johan H. M.; Huinck, Wendy J.; Van Zanten, Gijsbert A.; Grolman, Wilko (Frontiers in Surgery, 2017)
Importance There is an ongoing global discussion on whether or not bilateral cochlear implantation should be standard care for bilateral deafness. Contrary to unilateral cochlear implantation, however, little is known about the effect of bilateral cochlear implantation on tinnitus. Objective To investigate tinnitus outcomes 1 year after bilateral cochlear implantation. Secondarily, to compare tinnitus outcomes between simultaneous and sequential bilateral cochlear implantation and to investigate long-term follow-up (3 years). Study design This study is a secondary analysis as part of a multicenter randomized controlled trial. Methods Thirty-eight postlingually deafened adults were included in the original trial, in which the presence of tinnitus was not an inclusion criterion. All participants received cochlear implants (CIs) because of profound hearing loss. Nineteen participants received bilateral CIs simultaneously and 19 participants received bilateral CIs sequentially with an inter-implant interval of 2 years. The prevalence and severity of tinnitus before and after simultaneous and sequential bilateral cochlear implantation were measured preoperatively and each year after implantation with the Tinnitus Handicap Inventory (THI) and Tinnitus Questionnaire (TQ). Results The prevalence of preoperative tinnitus was 42% (16/38). One year after bilateral implantation, there was a median difference of −8 (inter-quartile range (IQR): −28 to 4) in THI score and −9 (IQR: −17 to −9) in TQ score in the participants with preoperative tinnitus. Induction of tinnitus occurred in five participants, all in the simultaneous group, in the year after bilateral implantation. Although the preoperative and also the postoperative median THI and TQ scores were higher in the simultaneous group, the median difference scores were equal in both groups. In the simultaneous group, tinnitus scores fluctuated in the 3 years after implantation. In the sequential group, four patients had an additional benefit of the second CI: a total suppression of tinnitus compared with their unilateral situation. Conclusion While bilateral cochlear implantation can have a positive effect on preoperative tinnitus complaints, the induction of (temporary or permanent) tinnitus was also reported. Clinical Trial Registration Dutch Trial Register NTR1722.